Local Wisdom-Based Disaster Mitigation Efforts in Grebeg Suran Sedekah Laut for Coastal Communities (A Folkloric Study in Mirit Sub-District, Kebumen District) - Utari, Rini; Fitriah, Annisa Gilang; Damayanti, Rike; Nugroho, Rudi Adi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
This research aims to analyse local wisdom on disaster mitigation in grebeg suran sedekah laut. The research was conducted to find disaster mitigation efforts that can be carried out by coastal communities based on local wisdom. This research used a qualitative approach with descriptive data type. The study used in this research is folklore studies. The participants in this research were community leaders who became key informants, fishing communities, and the general public in Mirit Subdistrict, Kebumen Regency. The data collection technique in this research is by conducting interviews. The results showed that grebeg suran sedekah laut consists of several series of processions and prayer poems that have fundamental meanings, functions, and roles for people's lives. The ritual structure of grebeg suran sedekah laut has a meaning that contains a form or effort of disaster mitigation based on local wisdom that can be utilised by the community to reduce the risk of disasters at sea. Disaster mitigation in the grebeg suran sedekah laut tradition is in the form of local knowledge about titen science and actions taken by the community. This research can be used as a means of educating the current generation about disaster mitigation efforts in grebeg suran sedekah laut and as cultural revitalisation.